Exploring the mid-Republican origins of Roman military administration - Pearson, Elizabeth H. (Historian), author.
1 online resource (viii, 217 pages)
Keywords: "This volume demonstrates the development of Roman military bureaucracy during the Middle Republic, expanding on recent research to examine these administrative systems that made possible Rome's expansion in this period. Bringing together literary works, epigraphy, archaeology, topography and demography, the study reveals a complex and well-structured bureaucratic system developing in parallel with the army during the Middle Republic, propelled in no small part by the stresses of the Hannibalic War. Not only the contents of documents, but the physical objects, individuals and spaces are discussed to recreate the administrative processes in maximum detail. Exploring the Mid-Republican Origins of Roman Military Administration provides an invaluable resource for students and scholars of Rome's military and administrative history, as well as anyone working on the Republican period"--